Perceived Importance and Existence of Career Development Practices in the Cambodian Context: Toward High School Students’ Future Careers Connectedness and Readiness - Sarom Mok; Sothea Lim (International Journal of Educational Innovation and Research, 2026)
While the importance of school counselors in fostering college connectedness and career readiness has been acknowledged in professional literature, little research has looked at how those in administrative and supervisory positions see their efforts. In light of this, the purpose of this study is to find out the perceptions of school directors and student’s supervisors of guidance on the importance and existing practices of career development in the Cambodian context. A total of 90 high school directors in Phnom Penh participated in this study. The instrument was adapted from the Directors and Supervisors of School Counselors Career Development Survey was given to members of the high school directors of guidance in order to assess their opinions regarding career development practices. Collected data were then analyzed by using the descriptive and inferential statistics via SPSS program. The findings revealed that the relationship between participant perceptions of importance and subsequent perceptions of existence of career development practices were statistically significant (r = .51; p < .001). It was also found that the predictive relationship between participant perceptions of importance and subsequent perceptions of the existence of career development practices were detected as statistically significant (B = 0.92, t (50) = 4.15, p < .001). This study helped shape future policy and current career development practices in high schools by offering insight into the ways that career development methods through school counselors need to be improved.